1967
DOI: 10.1136/bmj.3.5567.704
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte transformation and chromosome studies in Hodgkin's disease.

Abstract: P-araproteins-Hobbs NIEMC-JURA et al. (1964) found that after multiple passages the cells comprising the plasmacytoma could become considerably less differentiated, producing less paraprotein and growing faster. A few patients with obviously extensive rapidly growing myeloma similarly produce little or even no paraprotein, especially those who produce only Bence Jones protein.In lymphosarcomata and in chronic lymphatic leukaemia, on the other hand, it seems to be the rule that when paraprotein production oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1
2

Year Published

1968
1968
1976
1976

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 14 publications
(5 reference statements)
2
3
1
2
Order By: Relevance
“…In reticulum cell sarcoma, Stage IV, the impairment of transformation is remarkably similar to that observed in advanced cases of Hodgkin's disease, observed in this series, as well as that reported by others.3, 15, 17 T r u b o w i t P studied 8 patients with lymphosarcoma and reported that blast response to PHA did not differ from the control, although the data suggests reduction from control values in 3 cases. T h e differences observed between the control subjects, and patients with Hodgkin's disease and reticulum cell sarcoma were significant, in contrast to cases of lymphosarcoma.…”
Section: Discussionsupporting
confidence: 89%
“…In reticulum cell sarcoma, Stage IV, the impairment of transformation is remarkably similar to that observed in advanced cases of Hodgkin's disease, observed in this series, as well as that reported by others.3, 15, 17 T r u b o w i t P studied 8 patients with lymphosarcoma and reported that blast response to PHA did not differ from the control, although the data suggests reduction from control values in 3 cases. T h e differences observed between the control subjects, and patients with Hodgkin's disease and reticulum cell sarcoma were significant, in contrast to cases of lymphosarcoma.…”
Section: Discussionsupporting
confidence: 89%
“…The depression of PHA responsiveness persists for several months and it is also demonstrable in patients who had been continuously free from disease for more than 1 year after the initial course of treat ment. These data are at variance with those of Lawler et al [1967] and of H an and Sokal [1970], who showed normal lymphocyte responses within 3 months of completing a course of radiation, and suggest that the abnormal responses in remission patients, also noted by other workers [Levy and Kaplan, 1974], may be iatrogenic rather than disease related. However, in our study, remission patients showed generally better respon ses than patients who, at the time of the test, were relapsed.…”
Section: Discussioncontrasting
confidence: 55%
“…The data from which the figure was compiled include cases additional to those recorded here (Pentycross, 1968c). The cases with Hodgkin's disease have been published previously (Lawler et al, 1967).…”
Section: Transformation Studiesmentioning
confidence: 99%